Pharmacological and Interventional Approaches to Ascites Management in Cirrhosis: A Meta-Analysis - Annisa Ul Husni; Saptino Miro (HM Publisher, 2025)
Background: Ascites, a common complication of cirrhosis, significantly impacts patient morbidity and mortality. This meta-analysis evaluated the efficacy and safety of various pharmacological and interventional approaches for ascites management in patients with cirrhosis. Methods: A systematic search of PubMed, Embase, and Cochrane Library databases was conducted from January 2013 to December 2024, identifying randomized controlled trials (RCTs) comparing different pharmacological agents (diuretics, albumin, vasopressin receptor antagonists) and interventional procedures (large-volume paracentesis, transjugular intrahepatic portosystemic shunt [TIPS]) in cirrhotic patients with ascites. The primary outcome was complete ascites resolution. Secondary outcomes included time to ascites recurrence, adverse events, and mortality. A random-effects model was used to pool data, and heterogeneity was assessed using the I² statistic. Results: Twelve RCTs (n=2848 patients) met the inclusion criteria. Diuretics plus albumin was superior to diuretics alone in achieving complete ascites resolution (OR 2.18, 95% CI 1.65-2.88, p<0.001; I²=38%). Vasopressin receptor antagonists were comparable to diuretics plus albumin in terms of ascites resolution (OR 1.09, 95% CI 0.88-1.35, p=0.42; I²=12%) but associated with a lower incidence of hyponatremia (OR 0.52, 95% CI 0.35-0.78, p=0.002; I²=23%). Large-volume paracentesis was more effective than repeated small-volume paracentesis for ascites control (OR 1.75, 95% CI 1.31-2.34, p<0.001; I²=41%). TIPS was associated with a higher rate of complete ascites resolution compared to large-volume paracentesis (OR 2.45, 95% CI 1.78-3.38, p<0001; I²=35%) but a higher risk of hepatic encephalopathy (OR 2.21, 95% CI 1.48-3.30, p<0.001; I²=15%). Albumin reduced mortality in patients undergoing large-volume paracentesis (OR 0.68, 95% CI 0.49-0.94, p=0.02; I²=0%). Conclusion: This meta-analysis supports the use of diuretics plus albumin, vasopressin receptor antagonists, large-volume paracentesis, and TIPS for ascites management in cirrhosis, with the choice of therapy individualized based on patient characteristics, ascites severity, and the risk of complications.